Implementation of the Pancasila Student Profile (P5) Strengthening Project to Develop Students’ Attitude of Responsibility at State Elementary School 4 Karangrau - Ni’mah, Hayatun; Kuntoro, Kuntoro (Proceedings Series on Social Sciences & Humanities, 2025)
The purpose of this study was to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) in fostering students' attitudes of responsibility at Elementary School 4 Karangrau. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation of the implementation of P5 activities integrated into learning and school activities. The results showed that P5 activities provide opportunities for students to learn to be responsible through real activities, such as dividing tasks, managing joint activities, and reflecting on Pancasila values. The role of teachers as facilitators is very important in directing students to internalize the values of responsibility. The obstacles faced include limited time and resources, but can be overcome through collaboration between teachers and students. In conclusion, the implementation of the P5 Project contributes positively to the formation of students' responsible character gradually and sustainably.